2010
DOI: 10.1143/jjap.49.042501
|View full text |Cite
|
Sign up to set email alerts
|

Data Transmission Scheme with Spectral Switches of a Tilting Circular Mirror in Far Field

Abstract: An improved data transmission scheme that can be used for any chosen transmitting direction in free space is introduced. This scheme is obtained by analyzing the analytic form of the diffracted spectrum of a coherent broad band Gaussian spectrum incident on an adjustable tilting circular mirror. It is found that the transmitting angle and tilting angle are conjugate. The advantages of this method are that the transmission direction can be selected arbitrarily in advance and that it is easy to implement compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…Here we continue investigating the oblique incidence situation; consequently it is very interesting to find that the spectral shift can be controlled by the polarization state of the light, which is proposed for the first time as far as we know. The spectral control methods over a limited bandwidth light source have been both theoretically and experimentally studied extensively [2][3][4][5] and they are closely related to spectral anomalies [6,7], displaying strange spectral behavior caused by different mechanisms, such as aperture dispersion [8] or interactions between light and material [9]. The surface plasmons [10] can also produce spectral shifts for the p polarization.…”
Section: Introductionmentioning
confidence: 99%
“…Here we continue investigating the oblique incidence situation; consequently it is very interesting to find that the spectral shift can be controlled by the polarization state of the light, which is proposed for the first time as far as we know. The spectral control methods over a limited bandwidth light source have been both theoretically and experimentally studied extensively [2][3][4][5] and they are closely related to spectral anomalies [6,7], displaying strange spectral behavior caused by different mechanisms, such as aperture dispersion [8] or interactions between light and material [9]. The surface plasmons [10] can also produce spectral shifts for the p polarization.…”
Section: Introductionmentioning
confidence: 99%
“…T here are many interesting applications such as data transmission [1][2][3] or spatial-coherence spectroscopy 4) for spectral anomalies that are caused by diffraction of some apertures; 5) some of these applicatios are verified experimentally. 6) Another important application illustrated by the author is far field lattice spectroscopy, 7) and it is shown that the structure information for a lattice or periodic pattern can be obtained by measuring the diffracted spectrum of a broad-band light source at one spatial position in a far field.…”
mentioning
confidence: 97%